2009
DOI: 10.1186/1743-422x-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of immune responses and protective efficacy in mice after immunisation with Rift Valley Fever virus cDNA constructs

Abstract: Background: Affecting both livestock and humans, Rift Valley Fever is considered as one of the most important viral zoonoses in Africa. However, no licensed vaccines or effective treatments are yet available for human use. Naked DNA vaccines are an interesting approach since the virus is highly infectious and existing attenuated Rift Valley Fever virus vaccine strains display adverse effects in animal trials. In this study, gene-gun immunisations with cDNA encoding structural proteins of the Rift Valley Fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…The nucleocapsid (N) protein of RVFV encapsidates the three genome segments of the virus (the L, M, and S segments). It is considered a major immunogen and immunizations using the N antigen have been shown to evoke partial protective immunity in animal models [24][25][26]. The Gn and Gc glycoproteins protrudes from the surface of the virions and mediate attachment to the cell receptor [27].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleocapsid (N) protein of RVFV encapsidates the three genome segments of the virus (the L, M, and S segments). It is considered a major immunogen and immunizations using the N antigen have been shown to evoke partial protective immunity in animal models [24][25][26]. The Gn and Gc glycoproteins protrudes from the surface of the virions and mediate attachment to the cell receptor [27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, vaccination with N antigen has been shown to protect mice from wild-type RVFV challenge (Wallace et al 2006, Liu et al 2008, Lorenzo et al 2008, Lagerqvist et al 2009, Jansen van Vuren et al 2010, Lorenzo et al 2010. Remarkably, the glycoprotein Gne also showed an early-response reactivity (day 3 pv) in western blot and ELISA with MP12-vaccinated sera and was detected by day-28 pi sera from all ZH501-infected sheep.…”
Section: Figmentioning
confidence: 96%
“…2A). While nucleoproteins are not known to be directly involved in pathogenesis, experiments using recombinant N have shown it to elicit a partial degree of immune protection (37,42). Although strongly immunogenic, N cannot elicit neutralizing antibodies.…”
Section: Functional Characterization Of Rvfv Components and Their Rolmentioning
confidence: 99%
“…Although strongly immunogenic, N cannot elicit neutralizing antibodies. Furthermore, it has been shown that RVFV-immunized sheep and mice exhibit lymphocytic proliferation in vitro in the presence of recombinant N protein (37,42,43). This suggests that this level of immunity is mediated through the interactions of antigen-presenting cells (APCs) with T helper cells.…”
Section: Functional Characterization Of Rvfv Components and Their Rolmentioning
confidence: 99%